Chagas Disease Drug Discovery: Toward a New Era - Chatelain, Eric (Journal of biomolecular screening, 2015)
American trypanosomiasis, or Chagas disease, is the result of infection by the Trypanosoma cruzi parasite. Endemic in Latin America where it is the major cause of death from cardiomyopathy, the impact of the disease is reaching global proportions through migrating populations. New drugs that are safe, efficacious, low cost, and adapted to the field are critically needed. Over the past five years, there has been increased interest in the disease and a surge in activities within various organizations. However, recent clinical trials with azoles, specifically posaconazole and the ravuconazole prodrug E1224, were disappointing, with treatment failure in Chagas patients reaching 70% to 90%, as opposed to 6% to 30% failure for benznidazole-treated patients. The lack of translation from in vitro and in vivo models to the clinic observed for the azoles raises several questions. There is a scientific requirement to review and challenge whether we are indeed using the right tools and decision-making processes to progress compounds forward for the treatment of this disease. New developments in the Chagas field, including new technologies and tools now available, will be discussed, and a redesign of the current screening strategy during the discovery process is proposed.